Novel strongly coupled tungsten-carbon-nitrogen complex for efficient hydrogen evolution reaction. (4th January 2018) - Abbas, Syed Comail; Wu, Jing; Huang, Yiyin; Babu, Dickson D.; Anandhababu, Ganesan; Ghausi, Muhammad Arsalan; Wu, Maoxiang; Wang, Yaobing
Abstract: Alternatives to noble metal based electrocatalysts are vitally necessary to produce hydrogen from water at low overpotentials. Earlier research on tungsten based electrocatalyst has been mainly concentrated towards tungsten carbide (WC) and tungsten nitride (WN) as the potential electrocatalysts for hydrogen evolution reaction (HER), whereas tungsten carbide (W2 C) has been least focused upon. Herein, we report a highly active novel strongly coupled tungsten-carbon-nitrogen complex (W2 C-NC-WN complex) prepared by in situ carbonization method. This W2 C-NC-WN complex exhibits a remarkable electrochemical performance for HER with a small onset potential of 33 mV vs. RHE and requires an overpotential ( η ) of 145 mV vs . RHE to render −10 mA cm −2 current density. The Tafel analysis demonstrates a slope of 96 mV dec −1 which is much better than WN (109.6 mV dec −1 ) and WC (142.4 mV dec −1 ). The strong coupling of W2 C and WN within N-doped carbon (NC) framework brings about a significant enhancement in HER kinetics and faster electron transport due to the remarkable reduction in charge transfer resistance. The facile synthetic approach reported here, provides a powerful tool for the structurally controlled modification of the catalyst while simultaneously introducing active species. Graphical abstract: Highlights: A novel strongly coupled tungsten-carbon-nitrogen (W2 C-NC-NW) complex prepared by facile approach. W2 C-NC-WN complex exhibits a very low onset potential of 33 mV and an over potential of 145 mV. Low Tafel slope of 96 mV dec −1 endows fast HER kinetics and electron transport. The mechanism for HER activity of W2 C-NC-WN complex has been proposed.